Influence and implications of the renin–angiotensin–aldosterone system in obstructive sleep apnea : An updated systematic review and meta-analysis - Loh, Huai Heng; Chai, Chee Shee; Hziung Lim, Quan; Li Goh, Siew; Lee Ling, Lim; Anne, Yee; Norlela, Sukor (Wiley, 2022)
Obstructive sleep apnea is a chronic, sleep-related breathing disorder, which is an independent risk factor for cardiovascular disease. The renin–angiotensin–aldosterone system regulates salt and water homeostasis, blood pressure, and cardiovascular remodelling. Elevated aldosterone levels are associated with excess morbidity and mortality. We aimed to analyse the influence and implications of renin–angiotensin–aldosterone system derangement in individuals with and without obstructive sleep apnea. We pooled data from 20 relevant studies involving 2828 participants (1554 with obstructive sleep apnea, 1274 without obstructive sleep apnea). The study outcomes were the levels of renin–angiotensin–aldosterone system hormones, blood pressure and heart rate. Patients with obstructive sleep apnea had higher levels of plasma renin activity (pooled wmd+ 0.25 [95% confidence interval 0.04–0.46], p = 0.0219), plasma aldosterone (pooled wmd+ 30.79 [95% confidence interval 1.05–60.53], p = 0.0424), angiotensin II (pooled wmd+ 5.19 [95% confidence interval 3.11–7.27], p < 0.001), systolic (pooled wmd+ 5.87 [95% confidence interval 1.42–10.32], p = 0.0098) and diastolic (pooled wmd+ 3.40 [95% confidence interval 0.86–5.94], p = 0.0086) blood pressure, and heart rate (pooled wmd+ 3.83 [95% confidence interval 1.57–6.01], p = 0.0009) compared with those without obstructive sleep apnea. The elevation remained significant (except for renin levels) when studies involving patients with resistant hypertension were removed. Sub-group analysis demonstrated that levels of angiotensin II were significantly higher only among the Asian population with obstructive sleep apnea compared with those without obstructive sleep apnea. Body mass index accounted for less than 10% of the between-study variance in elevation of the renin–angiotensin–aldosterone system parameters. Patients with obstructive sleep apnea have higher levels of renin–angiotensin–aldosterone system hormones, blood pressure and heart rate compared with those without obstructive sleep apnea, which remains significant even among patients without resistant hypertension.